<h2>
<em><u>My</u></em><em><u> </u></em><em><u>equation</u></em><em><u> </u></em></h2>
<em>f</em><em>(</em><em>x</em><em>=</em><em>x</em><em>^</em><em>2</em><em> </em><em>is</em><em> </em><em>30</em><em> </em><em>and</em><em> </em><em>g</em><em>(</em><em>x</em><em>)</em><em> </em><em>=</em><em>4 1</em><em> </em><em> </em><em>is</em><em> </em><em>50</em><em>.</em><em>1</em>
<em>Hope</em><em> </em><em>it</em><em> </em><em>helps</em><em> </em><em>#brainliestbunch</em><em> </em><em>=</em><em>)</em><em> </em>
Replace u,x and y withyour values
u+xy=2+9*6=2+54=56
Answer:
a, b and d
Step-by-step explanation:
Answer:
Step-by-step explanation:
-5x + (x -1) = -21
-4x = -20
x = 5